Enhancing Biomass Production of Chlorella vulgaris in Anaerobically Digested Swine Wastewater Using Carbon Supplementation and Simultaneous Lipid Production - Chenkai Zhou; Mingmin Yuan; Cuifeng Huang; Qiqi Chen; Jiamin Wang; Xinting Chen; Hua Yang; Jun Fang; Bo Yang (Applied Sciences)
This study investigated anaerobically digested swine wastewater (ADSW) as a nutrient source for Chlorella vulgaris FACHB-8 cultivation under mixotrophic conditions with carbon supplementation. The microalgal strain was grown in ADSW supplemented with six carbon sources, followed by concentration optimization. Under optimized conditions (20 g/L glucose), FACHB-8 demonstrated a high biomass productivity (271.31 mg/L/day) and a specific growth rate of 0.42 per day. The system achieved an 88.70% total nitrogen removal and an 82.93% total phosphorus removal. The biomass contained 45.59% lipids, 29.72% proteins, and 13.05% carbohydrates, with fatty acid methyl esters showing balanced proportions of saturated (50.77%) and unsaturated fatty acids (49.23%). These findings highlight the potential of glucose-based mixotrophic cultivation for simultaneous wastewater treatment, renewable biomass production, and value-added lipid production. This work proposes a scalable swine wastewater treatment system that synergizes bioremediation and renewable energy production via carbon-enhanced microalgae cultivation, offering a dual-functional strategy for sustainable livestock wastewater reuse.